(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The research life cycle encompasses various stages, from the initial discovery of research questions to the final dissemination and assessment of results. Optimizing each stage is essential for enhancing productivity, ensuring accuracy, and maximizing the impact of research. This paper explores the tools and techniques available to researchers at each stage of the research life cycle. By integrating advanced technologies and adopting best practices, researchers can streamline their workflow, reduce errors, and enhance the overall quality of their research. This study is based on an extensive review of existing literature from leading academic databases and insights from global surveys on research tools.